Associations Between Vitamin D Levels and Risk of Heart Failure: A Bidirectional Mendelian Randomization Study - Gao, Ning; Li, Xuebiao; Kong, Minjian; Ni, Ming; Wei, Dongdong; Zhu, Xian; Wang, Yifan; Hong, Ze; Dong, Aiqiang (Frontiers in Nutrition, 2022)
Background: Although studies suggest that concentrations of serum 25-hydroxyvitamin D(25(OH)D) are lower in individuals with heart failure (HF), the beneficial effects of vitamin D supplementation are controversial. Therefore, in this study, we aimed to determine whether there is a causal relationship between serum VD levels and HF. Methods: Genetic instruments were obtained from genome-wide association studies of serum 25(OH)D level (n= 443, 734) and of HF (n= 977, 323), respectively. Two-sample bidirectional mendelian randomization analysis was performed with IVW as the primary method to infer causality. At the same time, a series of repeated analysis, sensitivity analysis, and instrumental variables (IVs) strength evaluations were carried out to verify the reliability of our results. Results: Mendelian randomized analysis showed that increased serum 25(OH)D was associated with a lower risk of HF in the IVW method. (odds ratio [OR]=0. 810;95%CI, 0. 697-0. 941, P=0. 006). In the reverse MR analyses, the genetic predisposition to HF was negatively correlated with serum 25(OH)D level (OR=0. 893;95%CI, (0. 821-0. 972), P=0. 009). Conclusion: Our study revealed the causal association between vitamin D levels and HF, which provided new evidence for VD supplementation therapy or adjuvant therapy for HF. At the same time, the level of serum 25(OH)D was expected to become a molecular marker for screening or judging the prognosis of HF.